Students’ Perceptions of Duolingo for Arabic Vocabulary Acquisition: A Case Study of Arabic Literature Students at Hasanuddin University - Amelia Puteri Yuswandi; Haeruddin Haeruddin; Zuhriah Zuhriah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Technological innovations have significantly influenced language learning approaches, particularly among Arabic Literature students. Duolingo, a gamified language learning application, has gained popularity for vocabulary development. However, its effectiveness in academic contexts remains underexplored. This study employed a mixed-methods design to assess Duolingo’s impact on vocabulary acquisition among 50 Arabic Literature students at Hasanuddin University. Participants completed pre- and post-tests over a two-week period of Duolingo use. Additionally, a questionnaire was administered to collect students’ perceptions of the app's usability and educational value. Findings revealed that 74% of students improved their vocabulary scores, with an average increase of 4.8 points. Students reported that Duolingo’s spaced repetition and gamification features enhanced motivation and vocabulary retention. However, 24% showed slight score declines, attributing this to the app’s limited focus on grammar, writing, and speaking—skills essential for academic success. While Duolingo supports vocabulary development through engaging and interactive methods, it falls short in providing comprehensive language instruction. These limitations suggest the necessity of integrating supplementary learning tools to support grammar and productive language skills. Duolingo can serve as a valuable supplementary tool for vocabulary learning but should not replace holistic language instruction. Future research should investigate the incorporation of artificial intelligence to enhance its capabilities in grammar and speaking skill development.